2011
DOI: 10.1016/j.nano.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Ag colloids and Ag clusters over EDAPTMS-coated silica nanoparticles: synthesis, characterization, and antibacterial activity against Escherichia coli

Abstract: To produce better antibacterial water-insoluble nanocomposites of silver (Ag), silver–silicon dioxide (Ag-SiO2) hybrid and silver colloid (Ag-c) nanoparticles (NPs) were studied. Ag-c NPs were synthesized using reduction of AgNO3, and Ag-SiO2 composites were prepared on a core of silica NPs functionalized with ethylenediamino-propyltrimethoxysilane, where Ag clusters were fabricated on amino groups using seed-mediated growth and characterized by transmission electron microscopy and ultraviolet-visible absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…In addition, it has also shown that Ag ? binds to functional groups of proteins, resulting in protein denaturation (Rastogi et al 2011). To obtain high biocompatibility and optimal antibacterial properties of the new compounds, silver ions were embedded in materials with bio-properties (Ciobanu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has also shown that Ag ? binds to functional groups of proteins, resulting in protein denaturation (Rastogi et al 2011). To obtain high biocompatibility and optimal antibacterial properties of the new compounds, silver ions were embedded in materials with bio-properties (Ciobanu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Type of nanoparticle Type of Salmonella Reference ASAP Nano-silver Solution Salmonella typhi (136) silver colloid nanoparticles Salmonella enteric (137) silver-silicon dioxide hybrid Salmonella enteric (137) ZnO nanoparticles Salmonella typhimurium (138) Spherical silver nanoparticles Salmonella typhimurium (139) Zinc oxide QuantumDots SalmonellaEnteritidis…”
Section: Metal Nanoparticles As Antisalmonellosis Agentsmentioning
confidence: 99%
“…This type of affinity has been used for adsorption of Au NPs or Ag NPs on support materials [30−33] . For example, Rastogi et al [30] prepared silica nanoparticle-supported Ag NPs by the reduction of Ag + in the presence of amino-functionalized SiO 2 nanoparticles. Mahanta and Valiyaveettil [33] reported that both Au NPs and Ag NPs can be adsorbed on amino-functionalized polyvinyl alcohol electrospun fibers obtained by esterification with lysine.…”
Section: Introductionmentioning
confidence: 99%